Penetrating the Creative Dimensions of Modern Thai Architecture - Horayangkura, Vimolsiddhi (Journal of Architectural/Planning Research and Studies (JARS), 2002)
Through analizing various impending factors within the contexts of Thai society, fundamental issues concerning the lack of creation of architecture in modern Thai character are pointed out. The new creative dimensions of modern Thai Architecture, appropriate to the modern Thai society, are then introduced. In-depth investigations are made regarding to the underlying induction and the specific approach in generating modern Thai architecture in terms of current determining factors and related conceptual framework. More significantly, the strategies of implementing the creative works are succinctly proposed. A special emphasis is given to the appropriate application of modern technology in conjunction with Thai wisdom and local contexts. It is expected that this presentation, in similar to those of other disciplines, would eventually lead to some conclusive dimensions for the creation of Thai arts as a whole.